2016
DOI: 10.1038/tpj.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the association between the GNB3 C825T polymorphism and metabolic disturbance in bipolar II patients treated with valproate

Abstract: This longitudinal study aimed to investigate the associations between the polymorphisms of guanine nucleotide-binding protein subunit β-3 (GNB3) C825T and metabolic disturbance in bipolar II disorder (BP-II) patients being treated with valproate (VPA). A 100 BP-II patients received a 12-week course of VPA treatment, and their body weight and metabolic indices were measured. At baseline, the GNB3 C825T polymorphisms were associated with the triglyceride level (P=0.032) in BP-II patients. During the VPA treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In addition, obesity in women with BD may be a side effect of mood stabilizers. Many studies have also confirmed the association between long‐term treatments of valproate and elevated risk of obesity, weight gain, type 2 diabetes, and dyslipidemia (P. S. Chen et al, ; Petty et al, ; Rehman, Sachan, & Chitkara, ; Verrotti, la Torre, Trotta, Mohn, & Chiarelli, ). Another study found the sex‐related pharmacokinetic differences of valproate, showing that valproate‐treated women without contraceptive therapy have longer lag times, lower hepatic outputs, and higher reabsorbed fraction than men (Ibarra, Vázquez, Fagiolino, & Derendorf, ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, obesity in women with BD may be a side effect of mood stabilizers. Many studies have also confirmed the association between long‐term treatments of valproate and elevated risk of obesity, weight gain, type 2 diabetes, and dyslipidemia (P. S. Chen et al, ; Petty et al, ; Rehman, Sachan, & Chitkara, ; Verrotti, la Torre, Trotta, Mohn, & Chiarelli, ). Another study found the sex‐related pharmacokinetic differences of valproate, showing that valproate‐treated women without contraceptive therapy have longer lag times, lower hepatic outputs, and higher reabsorbed fraction than men (Ibarra, Vázquez, Fagiolino, & Derendorf, ).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, obesity in women with BD may be a side effect of mood stabilizers. Many studies have also confirmed the association between long-term treatments of valproate and elevated risk of obesity, weight gain, type 2 diabetes, and dyslipidemia (P. S. Chen et al, 2017;Petty et al, 2014;Rehman, Sachan, & Chitkara, 2017;Verrotti, la Torre, Trotta, Mohn, & Chiarelli, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…VPA is a clinically available drug for the treatment of epilepsy and bipolar disorder. VPA has been shown to block voltage-dependent sodium channels, to act as a histone deacetylase (HDAC) inhibitor, and to inhibit NFKB activation, which may affect the immune response [19]. Therefore, we examined the inhibitory effect of VPA on NFKB activity in IM-resistant GIST cells and a xenograft animal model.…”
Section: Resultsmentioning
confidence: 99%
“…In bipolar populations, VPA response showed a positive association with XBP1-116 C/G polymorphism, but replication is needed (Kim et al 2009). GNB3 variants have also been associated with metabolic abnormalities in cross-over (Chang et al 2010) and prospective studies (Chen et al 2017) of BD patients treated with VPA.…”
Section: Valproic Acidmentioning
confidence: 99%